Evaluation of the Deposit System for Tax Payment within the Coretax System - Nugroho, Andri Adi; Rosid, Arifin (E-Jurnal Akuntansi, 2025)
This study evaluates the implementation of the Coretax deposit system using the OECD (2021) framework (relevance, effectiveness, impact, and sustainability) for research question indicators. A descriptive qualitative evaluation case study method was used for data collection and analysis. The study involved taxpayers and tax officers at KPP Madya Dua Jakarta Utara. The results showed that the relevance criterion was met, as the system effectively addressed taxpayers' administrative needs. The sustainability criterion was met because taxpayers expressed their commitment to continue using this system, citing its long-term benefits. The effectiveness criterion has not been fully met due to technical obstacles, including failures to update ledger balances in real time and an automatic FIFO-based deduction mechanism that creates the potential for interest penalties. The impact criterion has not been met because the deposit system does not change behavior; it is only a formality to avoid late penalties when technical obstacles arise